ELBOW JOINT EXAMINATION TECHNIQUE WITH CLINICAL DISLOCATION OF NON COOPERATIVE PATIENTS WITH LATERAL EXAMINATION AT THE RADIOLOGY UNIT OF AWAL BROS PANAM HOSPITAL - Rona Fadila; Fauzan Andrizal (Medical Imaging and Radiation Protection Research Journal, 2025)
Elbow joint radiography is a diagnostic imaging examination that utilizes X-rays to evaluate theanatomical structures of the elbow joint and identify abnormalities, including dislocations. Standardelbow joint radiographic examination is generally performed using two projections, namelyanteroposterior (AP) and lateral. In the lateral projection, the elbow is normally flexed to approximately90° to provide optimal visualization of the joint space and surrounding anatomical structures. However,in patients with elbow dislocation who are uncooperative due to severe pain or trauma, standardpositioning cannot always be achieved. In such cases, modification of the radiographic technique isnecessary to ensure patient safety while maintaining diagnostic image quality. This study aimed todescribe the radiographic examination technique of the elbow joint in a non-cooperative patient with aclinical diagnosis of elbow dislocation at the Radiology Unit of Awal Bros Panam Hospital.This study employed a qualitative descriptive design using a case study approach. Data were collectedthrough direct observation of the examination procedure, interviews with radiographers andradiologists, and documentation of the radiographic examination. The examination did not requirespecific patient preparation other than removing metallic objects that could produce image artifacts.Radiographic imaging was performed using AP and modified lateral projections. Because the patientwas non-cooperative and unable to tolerate elbow flexion, the lateral projection was obtained with theelbow maintained in an extended position.The findings demonstrated that modification of the lateral projection successfully produced diagnosticimages sufficient to evaluate the elbow joint and confirm the presence of dislocation. Therefore,adapting radiographic positioning according to the patient's clinical condition is essential for achievingoptimal diagnostic outcomes while prioritizing patient comfort and safety.